Theology : A Very Short Introduction - Ford, David F. (Oxford, New York Oxford University Press, 2013)
This is an introduction to the subject of academic theology. Its basic approach is interrogative, raising key questions so as to lead into a range of selected topics such as knowledge community, salvation, God, prayer and evil.
Include Index and Illustration
Keywords: Theology -- Theology, Doctrinal -- Religions